Role of positron emission tomography/computed tomography in living donor liver transplantation for hepatocellular carcinoma - Lee, Seung Duk (Hepatobiliary Surg Nutr, 2016)
Living donor liver transplantation (LDLT) becomes an important option for treatment for patients with hepatocellular carcinoma (HCC). With the advance of imaging modalities such as computed tomography (CT) and magnetic resonance image (MRI), preoperative staging and diagnosis for HCC was improved in LDLT. However, morphological characteristics based on the tumor number and size do not represent the tumor pathology and prognosis clearly. Therefore, many criteria using various markers have been reported, but still have limitation to predict the pathology and prognosis. Recently, 18F-fluorodeoxyglucose-positron emission tomography/CT (18F-FDG PET/CT) was introduced to have the usefulness for detection of extrahepatic metastases and prediction of post-transplant prognosis in liver transplantation (LT). Furthermore, the hybrid concept with both biologic activity using PET/CT and morphologic tumor characteristics using CT and MRI was reported to be selection criteria for the patient with HCC waiting LDLT. We will discuss the role of 18F-FDG PET/CT in LDLT as various aspects including tumor detection, pathology prediction, prognosis prediction, and possibility of selecting criteria.